Augmented Reality Game-Based Learning, Spatial Ability, and Learning Style: An Explanatory Mixed Methods - Hendri Handoko; Reo Al Farizi (MASI Mandiri Edukasi, 2026)
This study investigates the effectiveness of Augmented Reality Game-Based Learning (AR-GBL) in enhancing seventh-grade students’ spatial ability in geometry, using an explanatory mixed-methods design. The quantitative phase employed a quasi-experimental post-test-only control-group design involving 52 students from a public junior high school in Cirebon City, Indonesia. The experimental group received geometry instruction on flat-faced three-dimensional solids through AR-GBL, while the control group was taught conventionally. Data were collected using a spatial ability test and analysed through independent-samples t-tests, mastery analysis, and simple linear regression. The results indicate a statistically significant difference in spatial ability between groups (p < 0.05), with AR-GBL contributing 32.9% of the variance in students’ spatial performance and enabling both classical and individual mastery. The qualitative phase consisted of semi-structured student interviews and classroom observations to explain the quantitative results. Qualitative findings reveal that AR-GBL supported spatial understanding by strengthening three-dimensional visualization, facilitating mental rotation, increasing engagement, and enabling teacher-mediated reflection during learning activities. At the same time, initial technological adaptation and attentional regulation emerged as constraints that influenced individual learning trajectories. Integration of quantitative and qualitative findings shows that AR-GBL operates as a mediated learning environment rather than an autonomous instructional solution. These findings underscore the importance of pedagogical scaffolding to maximize the benefits of AR-based game-based learning for spatial ability development in geometry classrooms.